Toward a chilean phraseology - Matus Olivier, Alfredo (2013)
The formation of phrases has a higher frequency than it has been so far attributed in the communicative interplay. It has always been the focus of attention of interlinguistics, though not much in the teaching of a mother tongue. It has a relevance of first order in the process of fine semantic discrimination, in the metaphorization process, and in the distinctivity of idiomatic phrases. Here the discussion focuses on the lexicological condition of some phraseological items, on the delimitation of units which can be lexicographically arranged in the continuum where they work, and on the diatopic and diastratic variability of their distribution. We proposed to define some of the lexicographical options essential for the processing of phraseological material of the Spanish of Chile.